Determining the Alternative Type of Wood for Class a Fire Crib Test According to UL 2166 Standards - Shukor, J.âA. (Springer Science and Business Media Deutschland GmbH, 2022)
Wood is one of the primary combustible fuels used for Class A fire tests for clean agent fire suppression systems. The species classified in the standards, on the other hand, did not originate locally and are hardly found. It is overpriced to obtain in small quantities for the sake of the experimental test. Thorough investigations were suggested to validate the use of the proposed material, including verifying the species of the specimen, burning test, and conducting wood moisture content verification using oven-dry method to ensure the quality of combustible fuel for the final test as per standard requirement. The aim of this study is to justify the use of unspecified wood to meet the appropriate requirements for performing a fire crib test. As a result, the pinewood specifications were nearly and within the minimum criterion for performing the fire crib test. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.